2020
DOI: 10.21608/ejbo.2020.22970.1444
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profiles and Fuel Properties of Oils from Castor Oil Plants Irrigated by Microalga-treated Wastewater

Abstract: thus allowing the re-use of wastewater for the irrigation of plants that produce abundant bio-oils and for the irrigation of low-quality soils. Chlorella vulgaris was grown in Om El-Resh drain water as growth medium, after enrichment with nitrogen and phosphorous. Castor seeds were cultivated in a greenhouse at the Algal Biotechnology Unit, National Research Centre, Egypt. Fifteen days later, transplants were irrigated by untreated wastewater (WW); wastewater treated with microalgae (WW+A); or wastewater treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…3 (2021) the third hypothesis. In this concern, algal extract foliar applications is recommended for inducing plant growth under drastic stress conditions (Abdel-Maguid et al, 2004;2005;Shabaan et al, 2010;Tarraf et al, 2015;Enan et al, 2016;El-Sayed et al, 2018b;Anter andReda et al, 2020) which may exists in sandy soils subjected to prolong irrigations.…”
Section: Potassium Concentrations and Uptake In The Aboveground Plant Tissuesmentioning
confidence: 99%
“…3 (2021) the third hypothesis. In this concern, algal extract foliar applications is recommended for inducing plant growth under drastic stress conditions (Abdel-Maguid et al, 2004;2005;Shabaan et al, 2010;Tarraf et al, 2015;Enan et al, 2016;El-Sayed et al, 2018b;Anter andReda et al, 2020) which may exists in sandy soils subjected to prolong irrigations.…”
Section: Potassium Concentrations and Uptake In The Aboveground Plant Tissuesmentioning
confidence: 99%
“…Dinitrosalicylic acid (DNS) method was used to estimate the reducing sugars using glucose as a standard ( Miller, 1959 ). Lipid extraction was performed by Soxhlet extraction using n -hexane as a solvent ( Reda et al, 2020 ). Fatty acid methyl esters (FAMEs) were prepared and analyzed according to the modified method of Christie (1993) as describe previously ( Almarashi et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that increasing the microalgal biomass in urban wastewater might effectively lower the salinity because increased soil salinity and total dissolved solids (TDS) in UW could cause soil to become sodic [130]. As a result, UW that has undergone microalgal treatment is appropriate for fertigation or irrigation applications [131][132][133]. Even though the nutrient levels are reduced and the salinity is decreased, before being used for fertigation or irrigation after microalgal treatment, the presence of bacterial species, such as E. coli, intestinal nematodes, certain antibiotic-resistant bacteria, antibiotic-resistant genetic material, and several organic and toxic pharmaceutical compounds, may need to be maintained as per the prescribed regulation standards.…”
Section: Applications Of Microalgal-treated Wastewater (Mtw)mentioning
confidence: 99%